(untitled) (Applied Biological Research, 2012)
The present study was undertaken with the objective to study the correlation between different traits of aromatic rice and cause-effect relationship. Thirty aromatic rice genotypes were grown at Rice Research field, RAU, Pusa, Bihar, India in four environments (2 dates of sowing for 2 years i.e. kharif 2008 and 2009). Observations on 21 morphophysiological and quality traits were recorded. Grain yield showed significant but positive association with effective tillers plant-1, filled grains panicle-1, grain weight panicle-1, leaf area index and harvest index. The genotypic and phenotypic correlation showed similar trend of association, except for a few combinations. The component traits of grain yield in aromatic rice genotypes were harvest index, grain weight panicle-1, effective tillers plants-1, filled-grain panicle-1and leaf area index. The selection based on these component traits may increase the grain yield in aromatic rice. Leaf area index may be a preferable selection criterion due to its high positive indirect effects via kernel length towards yields along with other component characters with high direct effects towards yield.